Potentialities and challenges of land regularization in favelas and informal settlements: Exploring the use of unmanned aerial vehicles (UAVS) - Fantin, Marcel; Pedrassoli, Julio Cesar; Zaratine, William Nelli; Coelho, Ivan Langone Francioni; Melo, Breno Malheiros de (Seven Editora, 2023)
Land regularization in favelas is a challenging and complex issue in the Brazilian context, involving legal, social, economic and urban aspects. In this scenario, the use of unmanned aerial vehicles (UAVs), popularly known as drones, emerges as a promising tool with the potential to significantly assist in land regularization activities in informal settlements. This article aims to explore and highlight the potential of UAVs in the regularization of informal settlements, evidencing their ability to provide accurate, up-to-date and detailed geospatial information. UAVs can perform aerial photogrammetric surveys, capturing high-resolution images and generating georeferenced orthomosaics and 3d models of the areas of interest. However, the effective implementation of UAVs in land regularization faces several obstacles and challenges. One of the main challenges is the need for adequate standardization for the use of these technologies in slum areas, considering the particularities and specific demands of these settlements. In addition, issues related to privacy, security, access to the data collected and training of the professionals involved also require attention. Another relevant aspect is the gap between the scientific and technological research developed so far and the discussions on the right to housing. The research has been directed, for the most part, to meet the demands of financial capital, with emphasis on the agribusiness sector, leaving aside the needs of communities in situations of housing vulnerability. Therefore, it is essential to promote a closer integration between scientific research, legislation and public policies aimed at land regularization in favelas, in order to ensure that the use of UAVs is guided by ethical, inclusive and socially just principles. Only in this way will it be possible to fully harness the potential of these technologies to promote decent housing and access to fundamental rights in informal urban areas. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-028